Development of Mathematical Model of the Main Apparatus of the Oil Fractionation Unit - Safarova, A.A. (Herald of Azerbaijan Engineering Academy, 2024)
Currently, due to the rapid growth in demand for fuel and energy resources in the world, there is an increase in the depth of processing and an improvement in quality indicators at technological installations that carry out oil fractionation at the oil refineries of our republic. Increasing their economic efficiency by reducing energy costs during oil refining is of national economic importance. Ensuring the implementation of this technological process in both safe and optimal modes, as a rule, directly depends on the level of construction of its automation system. For development high-quality automation systems and implement enterprise management in an optimal mode, it is necessary to develop mathematical models that can adequately describe the operating modes of its main technological devices. In the article a mathematical model was developed that ensures the optimal operating mode of the K-2 column, which is the main fractionating device of a primary oil refining installation and its quality was evaluted.